Voting Majorities in the Fund : Effects of Second Amendment of the Articles. (Pamphlet Series, 1977)
This paper discusses the voting majorities prescribed by the Second Amendment of the Articles for the adoption of decisions by the IMF. The IMF is an international organization in which member states do not have the same voting power. Under the original Articles of Agreement, each member had 250 basic votes and one additional vote for each part of its quota equivalent to 100,000 U.S. dollars of fixed gold value, namely, dollars of the weight and fineness in effect on July 1, 1944. The same formula will apply after the second amendment becomes effective, except that the special drawing right, as the IMF's unit of account, will be substituted expressly for the U.S. dollar of 1944.